Inventarisasi Tumbuhan Famili Euphorbiaceae Di Sekitar Herbarium Bandungense Sith ITB Jatinangor - Rucika Galvani Putri; Roy Hadiningrat Trisniaji Sutrisno; Zahra Nurazizah Al-Islami; Ateng Supriyatna (Jurnal Riset Rumpun Ilmu Tanaman, 2023)
Euphorbiaceae is an Angiosperm plant which has several varieties with one of the highest number of species. This plant is useful in industry and medicine. Characteristic of this plant has a gummy stem. This observation aims to determine the types of plants in the Euphorbiaceae family around the Bandungsense Herbarium SITH ITB Jatinangor on June 6 2023. Observations were carried out using the survey method and analyzed descriptively qualitatively. From the observations, it was found that 10 plant species belong to the Euphorbiaceae family, namely Acalypha siamensis, Euphorbia milli, Euphorbia hirta, Acalypha indica, Hevea brasiliensis, Phyllanthus urinaria, Phyllanthus niruri, Excoecaria agallocha, Euphorbia thymifolia Linn and Manihot esculenta. The results of the observations explain the characteristics of each plant, accompanied by personal documentation of the observations.